TEACHER’S ROLE AS A PROMOTER OF MULTICULTURAL PERSPECTIVE: A CASE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE - Absharini Kardena (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
In EFL context, diversity of students’ culture and background commonly contributes as one of problems in teaching and learning processes. Teaching EFL ideally is not only about teaching language but also teaching culture. It is based on a common premise in which these two parts are interrelated; the language is a part of the culture and the culture is a part of the language. Thus, teachers as language practitioners are supposed to be promoters of multicultural perspectives. The teachers are demanded to encourage the learners to be aware of culture while using English. Since many problems appeared in the real life because of misunderstanding of such cultural aspects, teaching culture for the learners is determined important. Therefore, the teachers have a role to teach and guide the students to tolerant of cultural conflict, to respect diverse culture, to avoid stereotyping others, and to develop materials of cross cultural. This paper, which is derived and further developed based on research conducted in 2013,  discusses and analyzes English teachers’ points of view related to their role as promoter of multicultural perspectives and its impact on students’ progress in learning English.